Hardy and Rellich Type Inequalities on the Complex Affine Group - Sabitbek, Bolys; Suragan, Durvudkhan (Eurasian Mathematical Journal, 2017)
In this paper, by using properties of the fundamental solution of the canonical right-invariant Laplacian, versions of Hardy and Rellich type inequalities are proved on the complex affine group.